Home-garden Ethnobotanical Studi on Stunting Cases in The Kalipuro Settlement, Banyuwangi - Budi Wahono; Luchman Hakim; Hartati Kartikaningsih (Asian Journal of Social and Humanities, 2023)
This study aims to describe and map the differences in ethnobotany of residential gardens with cases of stunting and without stunting. This research is both quantitative and qualitative. Data collection was carried out using semi-structured interviews and field observations at 20 points of the squared plot of vegetation observations which also became a source of information. The data obtained was then analyzed for vegetation using the Shannon-Wiener index method and the use value of species. The results showed that there were differences in preferences for the use of plants in local community settlements with cases of stunting and non-stunting. Utilization of plants with the highest UVs were in settlements with cases of stunting, namely Zingiber officinale, Pandanus amaryllifolius and Amorphophallus muelleri, while in the yards without stunting cases were Actinocarpus commansi Blanco, Magnolia acuminata (L.) , Moringa olefira Lam, and Artocarpus altilis (Parkison ex F.A.Zorn) Fosberg. Communities in settlements without stunting cases consume intensely sources of food from their garden plots, while people in settlements with stunting cases do not. In particular, Moringa plants are only found in residential yard gardens without stunting and are not found in settlements with stunting cases.